2018
DOI: 10.1111/jse.12444
|View full text |Cite
|
Sign up to set email alerts
|

Testing reticulate evolution of fourVitisspecies from East Asia using restriction‐site associated DNA sequencing

Abstract: Reticulate evolution is an important driving force of angiosperm evolution. It has been proposed as an important evolutionary process in Vitis L. subgenus Vitis. Events of natural hybridization and introgression of several taxa native to North America have been hypothesized and discussed. However, there is no convincing evidence of reticulate evolution reported for closely related Vitis taxa from East Asia. We aim to explore natural hybridization and introgression among four closely related Vitis taxa from Eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…We hence regard Vitis davidii as a more likely parental species than V. romanetii due to their geographic distribution and the highly similar glandular trichome morphology. Ma et al (2018Ma et al ( , 2020 also showed that Vitis adenoclada and V. davidii grouped in one clade in the nuclear phylogeny, consistent with our hypothesis.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…We hence regard Vitis davidii as a more likely parental species than V. romanetii due to their geographic distribution and the highly similar glandular trichome morphology. Ma et al (2018Ma et al ( , 2020 also showed that Vitis adenoclada and V. davidii grouped in one clade in the nuclear phylogeny, consistent with our hypothesis.…”
Section: Introductionsupporting
confidence: 90%
“…Li (1998) and Ren and Wen (2007) did not treat Vitis adenoclada Hand.-Mazz., which was described from Hunan by Han-del-Mazzetti (1925), in the Flora Reipublicae Ropularis Sinicicae and Flora of China treatments. Species delimitation of eastern Asian Vitis remains highly problematic (Li et al 1996;Wan et al 2008;Ma et al 2018Ma et al , 2020. Based on our recent field work and the examination of the type material and additional specimens, we herein propose to recognize the long-neglected Vitis adenoclada from southern China.…”
Section: Introductionmentioning
confidence: 93%
“…The TreeMix model [ 117 ], developed to address historical relationships, showed a good efficiency when employed to resolve the evolution of crops and their wild relatives [ 118 , 119 ], but also unravelled the intricate relationship between grape hybrids [ 81 ]. Furthermore, the D-statistics analysis (ABBA-BABA tests) have already been applied to detect introgression among sympatric populations of Asian grapes providing interesting findings [ 120 ] while inferential tools for historical demography such as Approximate Bayesian Computation (ABC) methods could be used to estimate different demographic parameters such as divergence times and migration rates.…”
Section: Introgression Between Wild and Domesticated Grapevinementioning
confidence: 99%
“…Wan et al, 2013;Liu et al, 2016;Ma et al, 2018a;Wen et al, 2018a). Nevertheless, several studies have resolved Vitis subgenus Vitis into two main clades corresponding to their geographic distributional areas in Eurasia and North America (e.g., Zecca et al, 2012;Klein et al, 2018;Ma et al, 2018b;Wen et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%